2018
DOI: 10.21776/ub.jpacr.2018.007.02.348
|View full text |Cite
|
Sign up to set email alerts
|

Study of Antocyanins Activity from Purple Sweet Potato for Reducing Apoptotic Cells Expression of The Cerebellum On Ischemic Stroke Rats

Abstract: This study was aimed to determine anthocyanin antioxidant performance with a dose of 2 cc/day based on the expression of apoptotic cells in ischemic stroke rats cerebellum. The research was conducted using ischemic stroke rats (Rattus norvegicus) that prepared by ligated for 3 h on the Common Carotid Artery (CCA) and External Carotid Artery (ECA) followed by reperfusion that is commonly known as MCAO (Middle Cerebral Artery Occlusion). The anthocyanin extract was characterized by LC-MS and its IC 50 was measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Both models of ischemia induction (global and focal) were applied in studies on the effects of ACN administration. Some studies reported their beneficial effect when administered before stroke induction [82,180,181,182,183,184], others after the stroke induction [165,185,186], while a third set of studies monitored the effects of ACN administration before and after stroke induction [81,187,188,189].…”
Section: Evidence For Anthocyanins’ Effects In the Prevention And mentioning
confidence: 99%
See 3 more Smart Citations
“…Both models of ischemia induction (global and focal) were applied in studies on the effects of ACN administration. Some studies reported their beneficial effect when administered before stroke induction [82,180,181,182,183,184], others after the stroke induction [165,185,186], while a third set of studies monitored the effects of ACN administration before and after stroke induction [81,187,188,189].…”
Section: Evidence For Anthocyanins’ Effects In the Prevention And mentioning
confidence: 99%
“…Studies regarding the effect of pre-administration of ACNs on stroke used purified ACNs [82,181,182] or even encapsulated ACNs available on the market [183] (Table 4) with the aim to elucidate the molecular mechanisms by which ACNs act (see Section 4). Two modalities of stroke induction were applied, most often used is MCA occlusion model of focal ischemia [82,180,181,182,183] and only a single study used bilateral common carotid artery occlusion (BCCAO), which is a model of global ischemia [184], while various ways to administer ACNs are applied (Table 4). In most experimental models, laboratory animals were tracked and subsequently sacrificed 24 h after reperfusion [82,182,183] and only in one study after 72 h [184].…”
Section: Evidence For Anthocyanins’ Effects In the Prevention And mentioning
confidence: 99%
See 2 more Smart Citations
“…Preclinical research has demonstrated that red berries supplementation exerts both neuroprotective functional and mechanistic effects, such as reversal of age-related decrements in cognition, enhancements of neuronal resilience, endothelial protection, and cerebral blood flow [ 53 ]. Anthocyanins in purple sweet potato alleviated ischemic stroke in rats by reducing apoptosis-inducing factor levels and other antioxidant mechanisms [ 55 ].…”
Section: Phytochemicals In Dark-colored Plant Foods and Their Antiagi...mentioning
confidence: 99%